Comparison of Acetabular Labral Reconstruction With 7-mm Tibialis Anterior Allograft and 5-mm Iliotibial Band Autograft at Minimum 2-Year Follow-up. Issue 5 (April 2022) - Kocaoglu, Baris; Paksoy, Ahmet Emre; Kayaalp, Asim; Cerciello, Simone; Ollivier, Matthieu P.; Seil, Romain
Background: Labral reconstruction has been described as a treatment option for irreparable labral tear. Labral graft size ranges from 5 to 7 mm 2 for reconstruction. A thicker labral graft could support mechanical stability and protect cartilage better. No study has compared the effect of graft thickness on clinical outcomes. Purpose/Hypothesis: The purpose of this study was to compare patient-reported outcomes between hips reconstructed with an autologous iliotibial band (AUITB; 5 mm 2 ) graft and with an allogenic tibialis anterior (ALTA; 7 mm 2 ) tendon graft. Our hypothesis was that hips reconstructed with a thicker allograft (7 mm 2 ) would have better clinical outcomes than those with a smaller autograft (5 mm 2 ). Study Design: Cohort study; Level of evidence, 2. Methods: A total of 42 patients (aged 21 to 54 years) underwent arthroscopic hip segmental labral reconstruction during the study period of January 2016 to November 2018. Twenty patients had reconstruction with AUITB grafts (5 mm 2 ) and 22 with ALTA grafts (7 mm 2 ). Both groups had minimum 2 year follow-up. Patients were evaluated with patient-related outcome scores: modified Harris Hip Score, Nonarthritic Hip Score, and Hip Outcome Score–Sports Specific. Pain evaluation was performed using a visual analog scale. Results: There were significant differences in all studied variables when comparing pre- and postoperative scores. Yet, there were no differences in terms of patient-related outcome scores between the groups postoperatively. Postoperative visual analog scale scores averaged 2.1 for the AUITB group vs 1.9 for the ALTA group ( P = .89); modified Harris Hip Score, 82.7 vs 83.3 ( P = .77); Nonarthritic Hip Score, 81.1 vs 82.2 ( P = .81); and Hip Outcome Score–Sports Specific, 81.6 vs 82.5 ( P = .67). Conclusion: No differences were found in terms of clinical outcomes between the 7-mm 2 ALTA graft and the 5-mm 2 AUITB graft. Both graft types and thicknesses might be considered comparable choices for primary reconstruction. Although a thicker-graft labral reconstruction seemed to have more ability to cover joint surface, clinical results did not show any superiority of a thicker graft whether it is autologous or allogenic.